2023
DOI: 10.3389/fpls.2022.1072717
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a genome-wide genetic linkage map and identification of quantitative trait loci for powdery mildew resistance in Gerbera daisy

Abstract: Powdery mildew (PM) is a common fungal disease in many important crops. The PM caused by Podosphaera xanthii has been the most challenging problem in commercial Gerbera (Gerbera hybrida) production globally, often leading to severe losses of crop yield and quality. A small number of PM-resistant breeding lines and cultivars have been reported in Gerbera, but the underlying genetics for PM resistance in Gerbera is largely unknown. Scarcity of genomic resources such as genetic linkage maps and molecular markers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that R 2 is often low in association with the analysis of complex quantitative traits, especially in heterozygous plants such [ 44 , 45 ], and gerbera is a typical heterozygous plant. SNP markers have been developed in recent years, but only a small fraction can be mapped to linkage groups, possibly because of the high heterozygosity of gerbera [ 23 , 24 ]. The lack of a genome further limits the molecular marker-assisted breeding of gerbera.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that R 2 is often low in association with the analysis of complex quantitative traits, especially in heterozygous plants such [ 44 , 45 ], and gerbera is a typical heterozygous plant. SNP markers have been developed in recent years, but only a small fraction can be mapped to linkage groups, possibly because of the high heterozygosity of gerbera [ 23 , 24 ]. The lack of a genome further limits the molecular marker-assisted breeding of gerbera.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we developed new EST-SSR markers based on transcriptomes and identified several molecular markers linked to flower color through association analysis, laying the foundation for the molecular marker breeding of gerbera [ 21 ]. Fu et al [ 23 ] and Bhattarai et al [ 24 ] also developed SNP markers and constructed a genetic map of gerbera. However, the high heterozygosity of gerbera limited the mapping of SNPs to linkage groups.…”
Section: Introductionmentioning
confidence: 99%